Net Terrestrial Radiative Heat Fluxes over India during Monsoon (MAUSAM, 1969)
Infrared radiative heat flux and instantaneous rate of temperature change have been computed for Indian, subcontinent for monsoon season by making use of the numerical method developed for the purpose. The effects of water Vapour alone have been considered. It is found that the radiative beat loss near the surface is minimum over the Western Ghats. Over northeast and northwest India, the radiative heat loss is relatively high. Also, the radiative cooling integrated from the surface upto 300 mb indicates a large cooling over northeast and northwest India (>loC per day) and relatively small cooling over the southern Peninsula (